2019
DOI: 10.1063/1.5118360
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-speed ion conductance microscopy

Abstract: Scanning ion conductance microscopy (SICM) can image the surface topography of specimens in ionic solutions without mechanical probe-sample contact. This unique capability is advantageous for imaging fragile biological samples but its highest possible imaging rate is far lower than the level desired in biological studies. Here, we present the development of high-speed SICM. The fast imaging capability is attained by a fast Z-scanner with active vibration control and pipette probes with enhanced ion conductance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…To further understand how genetic alterations cause the acquisition of malignant phenotypes, such as increased migration and invasiveness, we performed a nano-scale topography and mechanical property analysis using scanning ion conductance microscopy (SICM). An SICM analysis can create live images that simultaneously show topography and stiffness by contact-free scanning of the cell surface with a nanopipette that measures the ion migration through the pipette tip [ 25 ]. Notably, we observed a distinct topographic feature—a microridge structure—on the surface of AKT-common and AKF organoid cells, which actively fluctuate ( Fig.…”
Section: Main Subjectsmentioning
confidence: 99%
“…To further understand how genetic alterations cause the acquisition of malignant phenotypes, such as increased migration and invasiveness, we performed a nano-scale topography and mechanical property analysis using scanning ion conductance microscopy (SICM). An SICM analysis can create live images that simultaneously show topography and stiffness by contact-free scanning of the cell surface with a nanopipette that measures the ion migration through the pipette tip [ 25 ]. Notably, we observed a distinct topographic feature—a microridge structure—on the surface of AKT-common and AKF organoid cells, which actively fluctuate ( Fig.…”
Section: Main Subjectsmentioning
confidence: 99%
“…A recent study [40] revealed a significant contribution of electroosmotic flow and the SCD of the tip to the measured ion current when a large ion concentration gradient exists around a small aperture of the tip. To quantitatively analyze these contributions to the measured SICM data obtained under such conditions [41], information of the detailed tip geometry is indispensable.…”
Section: Importance Of Membrane On Tem Gridmentioning
confidence: 99%
“…In this paper we report the adaptation and optimization of a wide-range x , y , z -nano-positioner design previously developed for high-speed SICM imaging 12 , 16 for HS-AFM scanning. The improved design extends the scanner’s acquisition bandwidth and permits high-fidelity, low-noise imaging at 0.5 fps (100 Hz line rate) over a 36 × 36 µm 2 area, corresponding to a high scan speed of 7.2 mm/s.…”
Section: Introductionmentioning
confidence: 99%